ANALISIS KELAYAKAN FINANSIAL TARIF BUS TRANS KOETARADJA BERDASARKAN ABILITY TO PAY (ATP) - Dhuyufur Rahmani; Renni Anggraini; Irin Caisarina (Prodi Magister Teknik Sipil Unsyiah, 2018)
A fare is a cost that should be paid by the user of the public transportation. The fare is set by the operator who provides the service of the transportation. The aim of this study is to determine the characteristics of the respondents, to analyze the fare based on Ability to Pay (ATP), and to investigate financial feasibility of the ATP fare of Trans Koetaradja bus. The study focuses on Corridor I of Keudah-Darussalam Trans Koetaradja route. Primary data was obtained using questionnaire survey with Stated Preference (SP) method. The sampling technique is Stratified Random Sampling. The target population is the resident of Kutaraja, Kuta Alam and Syiah Kuala districts. The respondents are divided into school students, university students and elderly/disabilities. The results of this study suggest that the ATP fare of Trans Koetaradja service is Rp. 3.200 (school students), Rp. 3.300 (university students), Rp. 3.500 (general public) and Rp. 3.400 (elderly/disability). The estimated gross income by the operator from this ATP fare is Rp. 1.074.590.000/year. The estimated VOC is Rp.13.544.838.955/bus/year. The calculation of investment feasibility of NPV with the rate of Rp. 317.330.243, BCR is around 1,029. Return capital of the ATP’s fare in the year 2016 - 2026 is the 10th year. Return of financial capital is low (around 15 years). The value of IRR is 16,30% which is more than level of interest of IRR greater than 14%. The result of financial feasibility ATP’s fare, WTP and fare of Transportation Department Aceh (Trans Koetaradja bus) is favorable and feasible.